Design and Validation of Sleep Apnea Risk Assessment (SARA): A Screening Tool for Moderate-to-Severe Obstructive Sleep Apnea - Solecka, Sarka; Tomaskova, Hana; Chudy, Milos; Kostlivy, Tomas; Slonkova, Jana (Nature and science of sleep, 2025)
PURPOSE: We designed and validated a concise, efficient screening tool, the Sleep Apnea Risk Assessment (SARA), to identify patients at high risk of moderate to-severe obstructive sleep apnea. PATIENTS AND METHODS: We conducted a two-phase, multicenter study from September 1, 2018, to October 31, 2023. We created Cohort A (n=221, mean age 50.5±13.0 years, 69.2% male) to design SARA and compared the results with the Epworth Sleepiness Scale, Berlin Questionnaire, Pittsburgh Sleep Quality Index, STOP-Bang, and STOP questionnaires. Cohort B (n=253, mean age 48.0±13.4 years, 75.5% male) served for validation. RESULTS: SARA comprises six variables with the highest accuracy: sleep apnea observed by the bedroom partner (8 points), snoring (5 points), male sex (3 points), age≥50 years (3 points), daytime fatigue (3 points), and body mass index≥30 kg/m2 (2 points). SARA yielded an area under the receiver operating characteristic curve (AUC) of 0.77 (95% CI: 0.71-0.83) and sensitivity of 87.2% (95% CI: 80.8-92.1) in cohort A at a cut-off score of ≥11 points. Validation in cohort B showed an AUC of 0.79 (95% CI: 0.74-0.84) and a sensitivity of 98% (95% CI: 89.2-95.4). SARA performance significantly outperformed the other questionnaires tested. CONCLUSION: The SARA is a promising new screening tool for moderate-to-severe obstructive sleep apnea, demonstrating high sensitivity and a strong ROC curve. Further large-scale validation is recommended.
Keywords: SARA; obstructive sleep apnea; STOP-bang; Epworth sleepiness scale; Berlin questionnaire; screening questionnaire